HUBUNGAN KARAKTERISTIK DAN PENGETAHUAN IBU TENTANG GIZI DAN KMS (KARTU MENUJU SEHAT) DENGAN STATUS GIZI BADUTA USIA 6-24 BULAN DI WILAYAH KERJA PUSKESMAS KELURAHAN KALISARI TAHUN 2021 - Defshika Cahyanda Imrani, (2021)
Children aged 6-24 months are golden period, because of its rapid growth and development. They are need to get nutritional attention because they are very susceptible to malnutrition. One of the government efforts to overcome nutrition problems in Indonesia is by monitoring the growth on a regular basis and then assessing the result based on KMS (Healthy Card). The aim of this research is to know the correlation between mother's characteristics and knowledge about nutrition and KMS (Healthy Card) with nutritional status of children aged 6-24 months. This research used quantitive method with cross-sectional approach. This research was conducted at Kelurahan Kalisari Primary Health Care Area with a total sample of 272 people. The sampling technique was cluster random sampling. The result of the chi square statistical tests showed there were a correlation between mother's job (p=0,029), income (p=0,001), mother's knowledge of nutrition (p=0,001), and mother's knowledge of KMS (Healthy Card) (p=0,001) with with nutritional status of children aged 6-24 months. It hopes this research data could become the basis of intervention that will be held by the primary health care, and also the suggestion for the mother to increase their knowledge and attention to their children's growth and nutrition.